2021
DOI: 10.1093/cid/ciab716
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Cipargamin (KAE609) in a Randomized, Phase II Dose-Escalation Study in Adults in Sub-Saharan Africa With Uncomplicated Plasmodium falciparum Malaria

Abstract: Background Cipargamin (KAE609) is a potent antimalarial in a phase II trial. Here we report efficacy, pharmacokinetics, and resistance marker analysis across a range of cipargamin doses. These were secondary endpoints from a study primarily conducted to assess the hepatic safety of cipargamin (hepatic safety data are reported elsewhere). Methods This phase II, multicenter, randomized, open-label, dose-escalation trial was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 22 publications
1
44
0
Order By: Relevance
“…There was no obvious relationship between LFT abnormalities and cipargamin dose or exposure. Exposure to cipargamin in this trial was higher or comparable to previous trials [ 1 ], with no evidence of an increase in hepatic events. In addition, patients receiving both cipargamin and artemether–lumefantrine during the study did not show an increased rate of LFT abnormalities.…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…There was no obvious relationship between LFT abnormalities and cipargamin dose or exposure. Exposure to cipargamin in this trial was higher or comparable to previous trials [ 1 ], with no evidence of an increase in hepatic events. In addition, patients receiving both cipargamin and artemether–lumefantrine during the study did not show an increased rate of LFT abnormalities.…”
Section: Discussionsupporting
confidence: 73%
“…This study paves the way for the further development of this novel anti-malarial. In addition to the good tolerability of cipargamin, this study has confirmed its potency and rapid onset of parasiticidal activity with parasite clearance times of around 8 h for doses of 50 mg or higher [ 1 ]. Furthermore, cipargamin is potent against artemisinin-resistant parasites including the R561H mutant, which is spreading in Rwanda [ 2 ].…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations